Creating Learning Experience Model in Environmental Chemistry for High School Students - Rakthai, Saksri; Pramuanl, Phanuchai; Kasemsan, Warapol (Journal of Advanced Development in Engineering and Science, 2023)
The purposes of this study were 1) to analyze environmental chemistry content and 2) to create the Learning Experience in environmental chemistry for high school students. The samples consisted of 20 students in grade 12 from high school in Phetchaburi province Thailand. The data were collected by literature review and student?s achievement of pre- and post- Learning Experience Model implementation. Simple statistics including means and standard deviation were used for data analysis. The finding showed that environmental chemistry content was included in science?s learning area of the Basic Education Core Curriculum B.E. 2551 of Thailand. The content of the environmental chemistry in this study was improvement water quality by chemical process and the structures of Learning Experience were content, objective, learning situation, media and evaluation. The evaluation of student?s learning achievement found that the achievement of post learning was higher than pre learning and the satisfaction of learning experts on the structures of Environmental Chemistry Learning Experience was high with mean at 2.70 out of 3.00 and standard deviation (S.D.) was 0.20.